The Importance Of Food loss Mitigation Extension At Critical Points Of Chili Harvest And Post-Harvest - Ferry Rahmat; Rika Nalinda; Epsi Euriga (Politeknik Pertanian Negeri Samarinda, 2026)
Chili pepper is a strategic horticultural commodity with high vulnerability to food loss throughout its supply chain. This study aimed to assess the level of food loss mitigation implementation at five critical supply chain points and to analyze its effect on food loss levels among chili farmers in Umbulmartani Village, Sleman Regency, Yogyakarta. A quantitative descriptive method with multiple linear regression analysis was employed. Sixty farmers were selected through proportional random sampling from 15 farmer groups. Data were collected through structured interviews using a Likert scale 1–4 questionnaire. Mitigation implementation at harvesting (75.83%), sorting and cleaning (82.22%), packaging and transportation (79.17%), and storage (76.95%) fell in the high category, while loading-unloading (52.50%) was in the medium category. The average food loss reached 18.07% or 31 kg per farmer. All five mitigation variables simultaneously and significantly affected food loss (F = 5.329; sig. = 0.000; R² = 0.330). Partially, harvesting technique positively influenced food loss (B = 4.567; sig. = 0.000), while sorting and cleaning negatively affected it (B = −1.919; sig. = 0.031). It is concluded that strengthening GAP-based harvest techniques and improving GHP-based sorting practices through targeted extension programs are the most effective interventions to reduce chili food loss at the farmer level.